Estimating Monthly GDP In A General Kalman Filter Framework: Evidence From Switzerland - Nicolas A. Cuche; Martin K. Hess (Swiss National Bank, Study Center Gerzensee, 1999)
In this paper, we estimate deseasonalized monthly series for Swiss gross domestic product at constant prices of 1990 for the period 1980-1998. They are consistent with the quarterly figures estimated by the Federal Office for Economic Development and Labour and are obtained by including information contained in related series. We present a general approach using the Kalman filter technique nesting a great variety of interpolation setups. We evaluate competing models and provide a time series that can be used by other researchers.
Keywords: E32; E37; 330; Interpolation; Kalman filter; National accounting; Nationaleinkommen; Schätzung; Schweiz; Zustandsraummodell